2020
DOI: 10.3390/jcm9082460
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Factor Structure and Predictive Validity of the Widespread Pain Index and Symptom Severity Scales of the 2010 American College of Rheumatology Criteria of Fibromyalgia

Abstract: Fibromyalgia syndrome (FMS) is a chronic condition of widespread pain. In 2010, the American College of Rheumatology (ACR) proposed new diagnostic criteria for FMS based on two scales: the Widespread Pain Index (WPI) and Symptoms Severity (SS) scale. This study evaluated the reliability, factor structure and predictive validity of WPI and SS. In total, 102 women with FMS and 68 women with rheumatoid arthritis (RA) completed the WPI, SS, McGill Pain Questionnaire, Trait Anxiety Inventory, Fatigue Severity Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
(88 reference statements)
2
26
0
Order By: Relevance
“…28 In particular, ACR widespread pain index and ACR symptom severity scale allow for highly accurate identification and differentiation of fibromyalgia patients. 29 Our findings of high rates of generalised joint laxity in this population are in line with other studies of ME/CFS, however, ours is the first to directly compare diagnostic assessments for hypermobility. 13 Fibromyalgia and ME/CFS are both associated Beyond bones with inflammatory abnormalities and dysautonomia (eg orthostatic intolerance, postural orthostatic tachycardia syndrome and orthostatic hypotension), which is also commonly observed in symptomatic hypermobility.…”
Section: Discussionsupporting
confidence: 90%
“…28 In particular, ACR widespread pain index and ACR symptom severity scale allow for highly accurate identification and differentiation of fibromyalgia patients. 29 Our findings of high rates of generalised joint laxity in this population are in line with other studies of ME/CFS, however, ours is the first to directly compare diagnostic assessments for hypermobility. 13 Fibromyalgia and ME/CFS are both associated Beyond bones with inflammatory abnormalities and dysautonomia (eg orthostatic intolerance, postural orthostatic tachycardia syndrome and orthostatic hypotension), which is also commonly observed in symptomatic hypermobility.…”
Section: Discussionsupporting
confidence: 90%
“…The 1990 criteria have been considered as stricter than the 2010 criteria, such that only more severely affected patients are identified [2]. Studies recruiting FMS patients according to the 1990 ACR criteria reported higher mean WPI and SS scores than studies in which patients were recruited using the 2010 ACR criteria [2,72]. Nevertheless, a study which divided FMS patients into adapted (i.e., lower levels of psychological distress, catastrophizing, and fatigue) and maladapted profile (including problems in resilience, catastrophizing, and memory) found in the adapted profile subgroup a greater percentage of patients fulfilling the 1990 ACR criteria but not the 2011 criteria, whereas the opposite occurs in the maladapted profile subgroup.…”
Section: Associations Of Prevalence and Sex Ratio With The Different Diagnostic Criteriamentioning
confidence: 99%
“…Pain area and WPI were derived from electronic pain drawings acquired with the SymptomMapper application. 38 The WPI has been used for the diagnosis of fibromyalgia 34 , 39 and has been associated with central sensitization. 40 …”
Section: Methodsmentioning
confidence: 99%